The genus Tetracladium in Pampean streams (Buenos Aires, Argentina) - Kravetz, Sebastián; González, Beatriz; Marano, Agostina; Giorgi, Adonis (Phytotaxa, 2018)
Ingoldian fungi are frequently found in streams of the northern hemisphere, as well as in other regions worldwide. Even though they have high relevance as decomposers of fallen leaves, information on this group of fungi in Argentina is scarce. To assess the presence of ingoldian fungi in Pampean streams, samples of foam from 14 streams of different basins were collected. Four species and a new form of Tetracladium were recorded: Tetracladium breve, T. furcatum, T. marchalianum, T. setigerum and Tetracladium sp. Tetracladium furcatum is reported for the first time in South America, while T. breve and T. marchalianum are first records for Argentina.